Addressing Constipation in Head and Neck Cancer Patients Undergoing Radiotherapy: A Clinical Audit to Improve Management - Krishnamurthy, Sapna; Ahmed, Imtiaz (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: Constipation is a prevalent and often overlooked symptom in patients undergoing radiotherapy (RT) for head and neck cancer, leading to patient distress and potential treatment non-compliance. This clinical audit aimed to assess the burden of constipation and evaluate the effectiveness of a guideline-based management approach. Methods: This standard-based clinical audit was conducted in the Department of Radiation Oncology from July 2021 to January 2022, involving patients with constipation during RT for head and neck cancer. The intervention implemented followed the European Society for Medical Oncology (ESMO) 2018 flowchart for constipation management, divided into four key checkpoints: history taking, laxative documentation, symptom relief assessment, and maintenance therapy prescription. A standard of 65% adherence to these checkpoints was set. Results: A total of 48 patients were evaluated retrospectively and 44 prospectively. Constipation was reported by 32 (66.6%) patients in the initial assessment and 26 (60%) patients in the re-assessment. Prior to intervention, none of the ESMO flowchart checkpoints were consistently addressed, while after implementation, adherence significantly increased to 92% for history taking and laxative documentation, and 77% for symptom relief assessment and maintenance therapy prescription. The mean number of days for complete symptom relief decreased from 7 to 2 days, and the time to reporting constipation reduced from 5 to 3 days. The number of active reviews until symptom resolution increased from 0 to 2 times. Conclusion: Empirical management of constipation during RT for head and neck cancers is associated with poor outcomes. Implementing guideline-based treatment approaches, as outlined by the ESMO flowchart, resulted in significantly improved symptom control and patient care. These findings highlight the importance of a structured and proactive approach to managing constipation in this patient population.